KERAPATAN DAN PENUTUPAN LAMUN PADA DAERAH TANGGUL PEMECAH OMBAK DI PERAIRAN DESA TEREBINO PROPINSI SULAWESI TENGAH - Ira Ira; Dedi Oetama; Juliati Juliati (AQUASAINS, 2013)
Waters Terebino village has afairly extensive seagrass. However, since thebreakwater, seagrass density and percentcover is changes. This study aims to lookat the seagrass density and percent coveron a breakwater area. Results are expectedto provide useful information and relevantparties in an effort to manage a sustainablemarine biological resources and as a comparisonfor future research. Determinationof the presence of seagrass station basedaround a breakwater and compare with seagrasswhich there is no breakwater. Researchmethods using transect quadrant 50x 50 cm. The results showed that in thearea of seagrass that no breakwater dikehas a density and percent cover two timeshigher than the seagrass area contained abreakwater.